Pandas - Catton, Chris (New York : Facts on File Publications, 1990)
Relates how pandas were discovered, their habitat and behavior, and recent efforts to restore the panda's population in the wild.
Includes bibliographical references (p. [137]-145) and index.
Wilson's Junior High School.
Wilson's Public Library.
Wilson's Senior High School.
Young Adult
Keywords: Giant panda; Giant panda; Pandas; Giant pandas; Pandas